Accommodation‐based interventions for individuals experiencing, or at risk of experiencing, homelessness. Issue 2 (18th May 2021) - Keenan, Ciara; Miller, Sarah; Hanratty, Jennifer; Pigott, Terri; Hamilton, Jayne; Coughlan, Christopher; Mackie, Peter; Fitzpatrick, Suzanne; Cowman, John
Abstract: Background: Globally, almost 1.6 billion individuals lack adequate housing. Many accommodation‐based approaches have evolved across the globe to incorporate additional support and services beyond delivery of housing. Objectives: This review examines the effectiveness of accommodation‐based approaches on outcomes including housing stability, health, employment, crime, wellbeing, and cost for individuals experiencing or at risk of experiencing homelessness. Search Methods: The systematic review is based on evidence already identified in two existing EGMs commissioned by the Centre for Homelessness Impact (CHI) and built by White et al. The maps were constructed using a comprehensive three stage search and mapping process. Stage one mapped included studies in an existing systematic review on homelessness, stage two was an extensive search of 17 academic databases, three EGM databases, and eight systematic review databases. Finally stage three included web searches for grey literature, scanning reference lists of included studies and consultation with experts to identify additional literature. We identified 223 unique studies across 551 articles from the effectiveness map on 12th April 2019. Selection Criteria: We include research on all individuals currently experiencing, or at risk of experiencing homelessness irrespective of age or gender, in high‐income countries. The Network Meta‐Analysis (NMA) contains all study designs where a comparison group was used. This includes randomised controlled trials (RCTs), quasi‐experimental designs, matched comparisons and other study designs that attempt to isolate the impact of the intervention on homelessness. The NMA primarily addresses how interventions can reduce homelessness and increase housing stability for those individuals experiencing, or at risk of experiencing, homelessness. Additional outcomes are examined and narratively described. These include: access to mainstream healthcare; crime and justice; employment and income; capabilities and wellbeing; and cost of intervention. These outcomes reflect the domains used in the EGM, with the addition of cost. Data Collection and Analysis: Due to the diverse nature of the literature on accommodation‐based approaches, the way in which the approaches are implemented in practice, and the disordered descriptions of the categories, the review team created a novel typology to allow meaningful categorisations for functional and useful comparison between the various intervention types. Once these eligible categories were identified, we undertook dual data extraction, where two authors completed data extraction and risk of bias (ROB) assessments independently for each study. NMA was conducted across outcomes related to housing stability and health.Qualitative data from process evaluations is included using a "Best Fit" Framework synthesis. The purpose of this synthesis is to complement the quantitative evidence and provide a better understanding of what factors influenced programme effectiveness. All included Qualitative data followed the initial framework provided by the five main analytical categories of factors of influence (reflected in the EGM), namely: contextual factors, policy makers/funders, programme administrators/managers/implementing agencies, staff/case workers and recipients of the programme. Main Results: There was a total of 13, 128 people included in the review, across 51 reports of 28 studies. Most of the included studies were carried out in the United States of America (25/28), with other locations including Canada and the UK. Sixteen studies were RCTs (57%) and 12 were nonrandomised (quasi‐experimental) designs (43%). Assessment of methodological quality and potential for bias was conducted using the second version of the Cochrane Risk of Bias tool for Randomised controlled trials. Nonrandomised studies were coded using the ROBINS‐ I tool. Out of the 28 studies, three had sufficiently low ROB (11%), 11 (39%) had moderate ROB, and five (18%) presented serious problems with ROB, and nine (32%) demonstrated high, critical problems with their methodology. A NMA on housing stability outcomes demonstrates that interventions offering the highest levels of support alongside unconditional accommodation (High/Unconditional) were more effective in improving housing stability compared to basic support alongside unconditional housing (Basic/Unconditional) (ES=1.10, 95% confidence interval [CI] [0.39, 1.82]), and in comparison to a no‐intervention control group (ES=0.62, 95% CI [0.19, 1.06]). A second NMA on health outcomes demonstrates that interventions categorised as offering Moderate/Conditional (ES= 0.36, 95% CI [0.03, 0.69]) and High/Unconditional (ES = 0.22, 95% CI [0.01, 0.43]) support were effective in improving health outcomes compared to no intervention. These effects were smaller than those observed for housing stability. The quality of the evidence was relatively low but varied across the 28 included studies. Depending on the context, finding accommodation for those who need it can be hindered by supply and affordability in the market. The social welfare approach in each jurisdiction can impact heavily on support available and can influence some of the prejudice and stigma surrounding homelessness. The evaluations emphasised the need for collaboration and a shared commitment between policymakers, funders and practitioners which creates community and buy in across sectors and agencies. However, co‐ordinating this is difficult and requires sustainability to work. For those implementing programmes, it was important to invest time in developing a culture together to build trust and solid relationships. Additionally, identifying sufficient resources and appropriate referral routes allows for better implementation planning. Involving staff and case workers in creating processes helps drive enthusiasm and energy for the service. Time should be allocated for staff to develop key skills and communicate engage effectively with service users. Finally, staff need time to develop trust and relationships with service users; this goes hand in hand with providing information that is up to date and useful as well making themselves accessible in terms of location and time. Authors' Conclusions: The network meta‐analysis suggests that all types of accommodation which provided support are more effective than no intervention or Basic/Unconditional accommodation in terms of housing stability and health. The qualitative evidence synthesis raised a primary issue in relation to context: which was the lack of stable, affordable accommodation and the variability in the rental market, such that actually sourcing accommodation to provide for individuals who are homeless is extremely challenging. Collaboration between stakeholders and practitioners can be fruitful but difficult to coordinate across different agencies and organisations.